Works Like a Charm Incentive Rhetoric and the Economization of Everyday Life - McDonald, Robert O. (SUNY Series, Insinuations: Philosophy, Psychoanalysis, Literature Series, 2023)
Breaks the spell of economic thought by interrogating the widespread language and logic of "incentives" in public life from a Lacanian perspective